Targeted Delivery of Chemotherapeutic Agents for Osteosarcoma Treatment - Xie, Duoli; Wang, Zhuqian; Li, Jie; Guo, De-an; Lu, Aiping; Liang, Chao (Frontiers in Oncology, 2022)
Since osteosarcoma (OS) is an aggressive bone cancer with unknown molecular pathways of etiology and pathophysiology, improving patient survival has long been a challenge. The conventional therapy is a complex multidisciplinary management that include radiotherapy, chemotherapy which followed by surgery and then post-operative adjuvant chemotherapy. However, they have severe side effects because the majority of the medicines used have just a minor selectivity for malignant tissue. As a result, treating tumor cells specifically without damaging healthy tissue is currently a primary goal in OS therapy. The coupling of chemotherapeutic drugs with targeting ligands is a unique therapy method for OS that, by active targeting, can overcome the aforementioned hurdles. This review focuses on advances in ligands and chemotherapeutic agents employed in targeted delivery to improve the capacity of active targeting and provide some insight into future therapeutic research for OS.